CASTRATION PUNISHMENT FOR PERPETRATORS OF CRIMINAL OFFENSES OF SEXUAL VIOLENCE AGAINST CHILDREN - Endang Yuliana Susilawati (Universitas Slamet Riyadi, 2021)
The castration sentence that has been imposed as an additional punishment to provide a deterrent effect for perpetrators of sexual violence against children in mid-2019 by judges at the Sidoarjo District Court and the Surabaya District Court is interesting to examine. The research objective was to determine the effect of the nut on the perpetrator, as well as the effect of its prevention on society. This type of juridical normative research is descriptive in nature, with qualitative analysis. The results of the research show that the judge's decision has only had a panic effect on the perpetrator, it is not possible to see a deterrent effect for the perpetrator because castration will only be carried out when the convict has finished serving imprisonment. While the preventive effect for the community has not yet been seen, it is proven that currently the crime rate is still high.